Cone-Beam Computed Tomographic Assessment of Bone Thickness in the Mandibular Anterior Region for Application of Orthodontic Mini-Screws - Majid Shalchi; Zahra Dalili Kajan; Mohammad Shabani; Negar Khosravifard; Samar Khabbaz; Farnoosh Khaksari (Galenos Yayinevi, 2021)
Objective: To determine the proper zones for placement of orthodontic mini-screws, based on cone-beam computed tomography (CBCT) measurements in the anterior mandibular region.Methods: The current cross-sectional study was performed on CBCT images of 77 individuals in the age range of 18-60 years. Axial slices at the levels of 2, 5, and 8 mm from the cementoenamel junction (CEJ) of the mandibular anterior teeth were selected. Interdental distances were measured in the mesiodistal direction, parallel to the midline of the mandibular arch. Areas with more suitable width were investigated for measuring the minimum interdental space. On the reconstructed cross-sectional images, labiolingual thickness of the bone was measured at the levels of 2, 5, 8, and 11 mm from the CEJ. The Kruskal-Wallis test, Mann-Whitney test with Bonferroni correction, Welch test, and Tukey's multiple analogy test were used to analyze the data.Results: Mesiodistal and labiolingual distances between the roots in every measured region had the highest values at the levels of 8 and 11 mm from the CEJ. The highest measured values were related to the interdental region between the lateral incisor and canine teeth on both sides of the arch. There were no statistically significant differences between these values (P < .001).Conclusion: The lateral incisor-canine areas at the level of 8 mm from the CEJ are introduced as the optimal sites for placement of orthodontic mini-screws. In addition, the results recommend the application of mini-screws with 1.3-1.7 mm diameter and 5-7 mm length.